LITERATURE STUDY: ANALYSIS OF LEARNING FACILITIES IN THE PANDEMIC ERA ON THE EFFECTIVENESS OF ONLINE LEARNING IN ELEMENTARY SCHOOL - Conny Dian Sumadi; Arif Hidayat; Islamia Agustina (Widyagogik, 2022)
This study aims to examine the literature on the analysis of learning facilities in the pandemic era on the effectiveness of online learning in elementary schools. The method used in this study is a literature study by carrying out the identification, screening and eligibility process for 5 articles obtained through Google Scholar. The result of this research is that the most chosen and used means is whatsapp because it is more practical and easy to use for elementary school level and parents can supervise the learning process.